Barriers to Understanding Health Education in Patients with Diabetes Mellitus (DM) in Yogyakarta: Qualitative Study - Kusumo, Mahendro Prasetyo; Kusumawati, Wiwik (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2022)
Poor physical activity behavior has its roots in a lack of understanding of the importance of healthy living. This study explores health education barriers to controlling blood glucose in a patient with DM in primary health care. The Forum Group Discussion (n = 22) and interview (n = 5) methods were used to explore the patient’s desire to overcome educational barriers. Informants for the study were patients with DM aged between 26-69 years from two community health centers and two private health centers within Sleman Regency, Indonesia. The informants were then questioned about barriers to physical activity programs for controlling blood glucose. The data collected was analyzed using Opencode, and the results revealed that boring educational training is the leading cause of physical inactivity and dietary control in patients with DM. Furthermore, the use of formal language in delivering material is the cause of patient boredom to take part in the training. Also, limited health human resources have resulted in a lack of maximum education programs for patients with DM in Yogyakarta. Therefore, a tense atmosphere and the use of complex language have a negative impact on patients to change physical activity and control eating patterns.